Basic Life Support Training: The Effectiveness and Retention of The Distance-Learning Method - Nur, Rifdhani Fakhrudin; Prasamya, Erlangga; Ikhwandi, Arief; Utomo, Prattama Santoso; Sudadi (Indonesian Journal of Anesthesiology and Reanimation, 2023)
Introduction: Basic Life Support (BLS) training during the COVID-19 pandemic needed to be effective as well as prevent disease transmission between trainers and participants. The distance-learning method is one of the recommended modified training methods. However, there is still limited research that evaluates the effectiveness of the distance-learning method for BLS training for laypersons during the COVID-19 pandemic. Objective: To evaluate the effectiveness and retention of the distance-learning method for BLS training in improving the participant's knowledge and skills. Methods: This is a non-randomized quasi-experimental study (one group pre-test and post-test design). A total of 64 TAGANA (Taruna Siaga Bencana/disaster volunteer) members of Sleman Regency who had undergone the distance learning method for BLS training were the participants of this study. A knowledge questionnaire and observation checklist were prepared and tested for context validity by an expert group. Data on the participant's knowledge were collected before and after the training session, and data on the participant's skills were recorded after the training session. After the training, a social media group was created to provide a periodical refresher of the BLS materials and facilitate discussions between the speakers and the study's samples. Data on knowledge retention and skills were recorded six months post-training. Results: The distance-learning method for BLS training effectively increased the participants' knowledge of BLS, indicated by a significantly higher final knowledge score than before the training (Z=-6.904, p <0.001). The method also provided sufficient BLS skills, indicated by most of the samples (93.7%) passing the skill observation test even though no participant had attended a similar training before. Moreover, the participant's knowledge and skills scores were significantly lower six months after the training session than immediately after training (Z=-5.157, p <0.001; Z=-4.219, p <0.001). Conclusion: The distance-learning method for BLS training effectively increased the participant's BLS knowledge and skills. However, their knowledge and skills decreased at six months post-training. Overall, the distance-learning method has been proven as a promising alternative to BLS training during and after the COVID-19 pandemic.